Online education status at government and private dental college during COVID-19 pandemic in India: A comparative study - Hansika Popli; Manu Batra; Deeksha Gijwani; Anjali Ahuja (Wolters Kluwer Medknow Publications, 2022)
Introduction: Pandemic COVID-19 has spread all over the world very profligately in a short interval. This has had disturbed the main determinant of the future economics that is the education sector. India is a country with a vast number of colleges and dental colleges are a part of nurturing budding dentists. Aim: The aim of the study was to assess the status of online education at government and private dental colleges of India during a COVID-19 pandemic. Materials and Methods: This is a cross-sectional questionnaire-based study; conducted among the faculties of all Indian government and private dental colleges taking online classes for bachelor of dental surgery students. A pretested and validated questionnaire was sent to faculty members through a Google form. To assess the differences in perception among faculties of different colleges, the use of Chi-square test was done whereas descriptive statistics surveyed the frequency distribution. Results: More than 70% of faculty members both from private and government colleges agreed that tracking of students is difficult during online classes. A laptop was used by the maximum number of respondents, that is, government (77.8%) and private (81.5%) as the mode for taking online classes. About 50% of government faculties and 59.5% of private faculty members used zoom as an online platform tool for taking classes whereas others used the Google meet app for taking classes. Conclusion: The COVID-19 pandemic has paved the way for E-Learning in dental education in India. Faculties agree to complete the theory syllabus and conduct sessional examinations as an alternative during the lockdown period. However, they show strong reservations in carrying out practical/clinical simulations and university exams online.